Antibacterial Activity of Young Papaya Fruit Extract (Carica papaya L.) Against Acne-inducing Propionibacterium acnes - Purwandhini, Dhesy Dwi Retno; Asri, Mahanani Tri; Yakub, Pramita (LenteraBio : Berkala Ilmiah Biologi, 2024)
Acne is one of the skin disorders that often attracts the attention of teenagers and young adults. The inappropriate use of antibiotics in the treatment of acne can lead to resistance, thus requiring alternatives from natural ingredients that have the ability as antibacterials. This study was conducted to test the antibacterial properties of young papaya fruit extract against the growth of P. acnes and determine the optimal concentration of young papaya fruit extract in stopping the growth of P. acnes. Antibacterial testing used the pitting method with a completely randomized design (CRD). Data analysis using Kolmogorov-Smirnov test, One Way Anova test, and Duncan test showed that the treatment of young papaya fruit extract concentration had a positive effect on the growth of P. acnes and there were significant differences with other treatments. The results of testing the antibacterial activity of young papaya fruit extract with a concentration of 20%, 40%, and 60% produced an average inhibition zone sequentially of 4,60 ± 0,54 mm, 7,60 ± 0,54 mm, and 10,80 ± 0,83 mm so that the 60% concentration can provide optimal results in stopping the growth of P. acnes because it forms the largest inhibition zone. Thus, this study proves that young papaya fruit extract has antibacterial properties so that it can be applied as a natural acne medicine.